ChemInform Abstract: Synthesis of Cyclopropyl‐ and Cyclobutylpiperidines: Advanced Building Blocks for Drug Discovery. Issue 19 (21st April 2016) - Vyzir, Ivan I.; Iminov, Rustam T.; Tverdokhlebov, Anton; Tolmachev, Andrey A.; Shcherbatiuk, Andriy V.; Mykhailiuk, Pavel K.; Biitseva, Angelina V.
Abstract: A library of the title piperidines is obtained by Wittig reactions starting from readily available materials.